2017
DOI: 10.1016/j.gore.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4 germline gene mutation in a patient with epithelial ovarian: A case report

Abstract: BackgroundSMARCA4 is gene whose protein product participates in chromatin remodeling. Somatic mutations in this gene are associated with non-small cell lung cancer and malignant rhabdoid tumors, and both germline and somatic mutations are seen with small cell carcinoma of the ovary, hypercalcemic type. To date, there are no data identifying an association with more common epithelial carcinomas of the ovary.CaseThe patient is a 57-year-old female without any significant family history of cancer, diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In contrast, SCCOHT is predominantly associated with SMARCA4 (BRG1) mutations and rarely with SMARCB1 (INI1) 68, 95. SMARCA4 (BRG1) mutations can be regarded as the hallmark of SCCOHT although deleterious germline SMARCA4 mutation has been reported in one high grade serous carcinoma to date 96. A recent molecular study demonstrated that the genomic and epigenomic signature of SCCOHT are similar to those of AT/RT 97.…”
Section: Clinical Implications From Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, SCCOHT is predominantly associated with SMARCA4 (BRG1) mutations and rarely with SMARCB1 (INI1) 68, 95. SMARCA4 (BRG1) mutations can be regarded as the hallmark of SCCOHT although deleterious germline SMARCA4 mutation has been reported in one high grade serous carcinoma to date 96. A recent molecular study demonstrated that the genomic and epigenomic signature of SCCOHT are similar to those of AT/RT 97.…”
Section: Clinical Implications From Molecular Geneticsmentioning
confidence: 99%
“…Thereafter, Foulkes WD, et al 62 have suggested that SCCOHT should be renamed as malignant rhabdoid tumors of the ovary having SMARCA4 mutations. This conception is further supported by SMARCA4-deficient undifferentiated uterine sarcoma (malignant rhabdoid tumor of the uterus), which showed rhabdoid morphology, SMARCA4 loss by immunohistochemistry and recurrent SMARCA4 mutations and few other molecular alterations 96. However, Soslow RA and colleagues 36 think that the nomenclature change is premature currently due to the extensive accumulation of literatures under the traditional term SCCOHT.…”
Section: Clinical Implications From Molecular Geneticsmentioning
confidence: 99%
“…From the investigation of unclassified malignancies, somatic variation in SWI/SNF‐related, matrix‐associated, actin‐dependent regulator of chromatin, subfamily A, member 4 ( SMARCA4 ) is recognized as one of the driver mutations in undifferentiated tumors 6 . It is found on chromosome 19p13.2 and is part of the SWI/SNF chromatin‐remodeling complex consisting of 40 exons 7 . SMARCA4 encodes Brm/Swi2‐related gene 1 ( BRG1 ), a tumor suppressor and catalytic subunit of the SWI/SNF chromatin‐remodeling complex.…”
Section: Introductionmentioning
confidence: 99%
“… 6 It is found on chromosome 19p13.2 and is part of the SWI/SNF chromatin‐remodeling complex consisting of 40 exons. 7 SMARCA4 encodes Brm/Swi2‐related gene 1 ( BRG1 ), a tumor suppressor and catalytic subunit of the SWI/SNF chromatin‐remodeling complex. SWI/SNF complexes regulate many tumor‐suppressive processes, including DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, tumors with ARID1A mutations acquire sensitivity to pan-HDAC inhibitors, thus making ARID1A-bearing cancers attractive for HDAC-based therapy [ 70 ]. SMARCA4 is frequently (over 90%) mutated in ovarian small cell carcinomas of the hypercalcemic type [ 71 , 72 ], however, to our knowledge, the first case of a germline SMARCA4 mutation in a patient with HGSOC was recently reported [ 73 ]. Further investigation on the role and clinical applicability of SMARCA4 and ARID1A in HGSOC is warranted [ 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%